2020
DOI: 10.1371/journal.pone.0233831
|View full text |Cite
|
Sign up to set email alerts
|

Social support and mental health among health care workers during Coronavirus Disease 2019 outbreak: A moderated mediation model

Abstract: During the outbreak of Coronavirus Disease 2019 (COVID-19) all over the world, the mental health conditions of health care workers are of great importance to ensure the efficiency of rescue operations. The current study examined the effect of social support on mental health of health care workers and its underlying mechanisms regarding the mediating role of resilience and moderating role of age during the epidemic. MethodsSocial Support Rating Scale (SSRS), Connor-Davidson Resilience scale (CD-RISC) and Sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
180
5
31

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(271 citation statements)
references
References 50 publications
17
180
5
31
Order By: Relevance
“…The mental health of health care providers is of particular importance for ensuring proper care and treatment (24). Although the results of the present study did not show a signi cant difference in the components of the study between the two groups, but it showed that Covid-19 has reduced the quality of work life and increased fatigue and anxiety of all health care personnel.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The mental health of health care providers is of particular importance for ensuring proper care and treatment (24). Although the results of the present study did not show a signi cant difference in the components of the study between the two groups, but it showed that Covid-19 has reduced the quality of work life and increased fatigue and anxiety of all health care personnel.…”
Section: Discussioncontrasting
confidence: 69%
“…In each sub-scale, scores 2-4, 5-7, 8-10 and were considered as low, medium, and high, respectively. The eight components of QWL that were measured in this questionnaire include fair and adequate pay (questions 1-2), safe and healthy work environment (questions 3-4), providing opportunities for growth and continuous security (questions 5-8), rule of law in the organization (questions 9-12), social dependence of work life (questions [13][14], general living space (15)(16)(17)(18), social integration and cohesion (questions 19-21) and development of human capabilities (questions [22][23][24]. To determine the QWL, the score of eight dimensions of QWL, which was 24 to 120, was divided into three parts, each part having a distance of 32 units.…”
Section: Study Toolsmentioning
confidence: 99%
“…Age, which is also associated with greater personal and professional competence and experience, seems to allow health and emergency workers to block the intrusive aspects of the trauma, thus making them more committed to the intervention and less influenced by the consequences. In other words, this leads them to be less influenced by the intrusive components of their traumatic experiences [88]. However, age seems to be associated with higher arousal levels, and it seems likely that older workers have a greater awareness of the risks associated with the pandemic, as well as a greater sense of responsibility toward patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a survey study including 4,357 HWs in China found that their main concerns were family members and colleagues getting infected with COVID-19 [ 7 ]. Other cross-sectional studies in China found that perceived social support was associated with better mental health outcomes during the COVID-19 pandemic [ 8 , 9 ]. However, these studies employed close-ended questions and pre-determined scales for hypothesized risk factors, and further research is needed to identify additional factors that negatively and positively impact HW wellbeing inductively.…”
Section: Introductionmentioning
confidence: 99%